The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1007/s00170-024-13338-9
|View full text |Cite
|
Sign up to set email alerts
|

Wettability and microstructural evolution of copper filler in W and EUROFER brazed joints

Ignacio Izaguirre,
Javier de Prado,
María Sánchez
et al.

Abstract: In terms of wettability, active systems are characterized by a reduction in interfacial energy as the time at specific conditions is increased. This article aims to investigate the evolution of wettability and microstructure, which undergoes a critical transformation at temperatures and dwell times near brazing conditions due to their significant impact on resultant mechanical properties. The objective is to enhance wettability and prevent the formation of different phases that can occur rapidly within the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…On the other hand, the use of liquid state joining techniques usually reports higher interactions at the bonding interfaces. For example, I. Izaguirre et al reported copper penetration of the EUROFER97 grain boundary at the ERUFOER97/braze interface and the formation of a reaction layer at the W–braze interface, giving rise to a more complex microstructure [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the use of liquid state joining techniques usually reports higher interactions at the bonding interfaces. For example, I. Izaguirre et al reported copper penetration of the EUROFER97 grain boundary at the ERUFOER97/braze interface and the formation of a reaction layer at the W–braze interface, giving rise to a more complex microstructure [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%